Transitioning to Sustainable Cities and Communities - Hubert Klumpner; Klearjos Eduardo Papanicolaou; Georgeen Theodore (MDPI, 2024)
In developing alternative approaches to urban development in response to the societal challenge of living in ever-expanding cities, this Volume on the SDG11, Sustainable Cities and Communities, proposes the concept of an ‘Urbanising Earth'. We question the dominant model of Western cities and their resultant global warming, leading to the replacement of natural environments with artificial ones. The Volume features over twenty practical and metaphorical cases from experienced practitioners to emerging design thinkers, each of whom offer interconnected reflections on the research, design, and implementation of projects anchored in architecture and design arguments, promoting a more balanced view of the built and natural environment. These reflections, designed to engage readers, highlight the collective effort needed for sustainable urban development. The Volume aims to facilitate design as a learning process for society to reconcile human and environmental rights while celebrating the art of cultivating and living in this urban age. The right to education and housing can create synergies, providing parks and public spaces to underprivileged neighbourhoods. The overall aim is to connect thinking with actions, while considering what modernism in architecture and urban planning is today. In doing this, the Volume sheds light on the condition of contemporary design itself. We draw from limitless approaches to the fundamental challenges and critical discussions presented to us by this'Urbanising Earth'.